Cardiac cells stimulated with an axial current-like waveform reproduce electrophysiological properties of tissue fibers. (November 2022) - Monasterio, Violeta; Pueyo, Esther; Rodríguez-Matas, José Félix; Carro, Jesús
Highlights: Inter-cellular coupling effects should be considered to ensure the trustworthiness of electrophysiological cardiac model predictions. An axial current-like waveform is proposed to stimulate single-cell cardiac models The proposed waveform is able to reproduce tissue-like AP properties Its use will improve the credibility of model predictions when single-cell AP markers are to be compared with tissue-derived reference values Abstract: Background and objective: In silico electrophysiological models are generally validated by comparing simulated results with experimental data. When dealing with single-cell and tissue scales simultaneously, as occurs frequently during model development and calibration, the effects of inter-cellular coupling should be considered to ensure the trustworthiness of model predictions. The hypothesis of this paper is that the cell-tissue mismatch can be reduced by incorporating the effects of conduction into the single-cell stimulation current. Methods: Five different stimulation waveforms were applied to the human ventricular O'Hara-Rudy cell model. The waveforms included the commonly used monophasic and biphasic (symmetric and asymmetric) pulses, a triangular waveform and a newly proposed asymmetric waveform (stimulation A) that resembles the transmembrane current associated with AP conduction in tissue. A comparison between single-cell and fiber simulated results was established by computing the relative difference between the values of AP-derived properties at different scales, and by evaluating the differences in the contributions of ionic conductances to each evaluated property. As a proof of the benefit, we investigated multi-scale differences in the simulation of the effects induced by dofetilide, a selective I K r blocker with high torsadogenic risk, on ventricular repolarization at different pacing rates. Results: Out of the five tested stimulation waveforms, stimulation A produced the closest correspondence between cell and tissue simulations in terms of AP properties at steady-state and under dynamic pacing and of ionic contributors to those AP properties. Also, stimulation A reproduced the effects of dofetilide better than the other alternative waveforms, mirroring the 'beat-skipping' behavior observed at fast pacing rates in experiments with human tissue. Conclusions: The proposed stimulation current waveform accounts for inter-cellular coupling effects by mimicking cell excitation during AP conduction. The proposed waveform improves the correspondence between simulation scales, which could improve the trustworthiness of single-cell simulations without adding computational cost.